Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.2174/1874844901603010182
|View full text |Cite
|
Sign up to set email alerts
|

Study of Effect of Different Factors in Formulation of Micro and Nanospheres with Solvent Evaporation Technique

Abstract: Background: There are various methods of formulation of micro and nanospheres such as solvent evaporation, solvent removal, polymerization, hot-melt encapsulation, coacervation, phase/wet inversion, spray drying, spray congealing etc. Amongst these all, solvent evaporation is one of the most widely used, researched, easy, accessible methods and for which many patents have been applied. It is thus imperative to understand the basics of effect of formulation variables and design of solvent ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 51 publications
2
20
0
Order By: Relevance
“…In this case, when the stirring rate is higher, a finer dispersion of the microparticles was formed, and the diminution of the particles' size leads to the drug release increase. The phenomenon is considered as normal because when the microparticles size decreased, the surface contact of microparticles with the release medium increased, and so the drug is rapidly dissolved and released …”
Section: Resultsmentioning
confidence: 99%
“…In this case, when the stirring rate is higher, a finer dispersion of the microparticles was formed, and the diminution of the particles' size leads to the drug release increase. The phenomenon is considered as normal because when the microparticles size decreased, the surface contact of microparticles with the release medium increased, and so the drug is rapidly dissolved and released …”
Section: Resultsmentioning
confidence: 99%
“…The 2-ABZT loaded microspheres were prepared by the (O/W) emulsion solvent evaporation method. 24 The preparation was realized by varying the parameters, i.e., the matrix type (EC or CAB), polymer/solvent ratio (polymer concentration in dichloromethane, 3, 5 and 6 wt. %), stirring speed and blades number (six and four-blade turbine impellers).…”
Section: Preparation Of Cellulose Derivatives Microspheresmentioning
confidence: 99%
“…These systems provide a pH-dependent drug release mechanism. [20][21][22] In drug microencapsulation, [23][24][25] the most used class of hydrophobic polymers is cellulose derivatives including ethyl cellulose (EC) and cellulose acetate butyrate (CAB) for a prolonged release. 26 Jelvehgari et al have shown that CAB formulations exhibit enough buoyancy to reside in the stomach over a prolonged and slower drug release.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Size is one of the most important factors that should be considered in the design and development of this system as size affects the interaction with the biological system, entry of the drug and drug release. Another important parameter is the entrapment efficiency (EE) which in turn related to the productivity of the pharmaceutical system [13]. The extract loaded ethyl cellulose microspheres were prepared successfully by o/w emulsion solvent evaporation method.…”
Section: Formulation Of Microspheresmentioning
confidence: 99%